Usaha Menyeimbangkan Otak Kiri Dengan Otak Kanan Bagi Anak - Mendrofa, Yason; Parhusip, R.L. Holmes; Heryanto (Fakultas Ilmu Pendidikan Universitas Sari Mutiara Indonesia, 2022)
It is an honor for parents and children themselves if the child has high ability in the field of exact sciences in the form of natural sciences and mathematics, but this is not realized that the child is only encouraged to develop left brain activities but the right brain seems to be neglected. As it is known that the human brain basically consists of two left and right hemispheres which ave different functions. The right brain tends to be related to E, interaction, communication with others, self-control, values and the nature of things. Meanwhile., the left brain tends to focus on logic, the ratio of writing, reading and mathmeatics. Between these two with different functions there is nothing wrong and both are useful. Because of that, there needs to be a balance to develop this function so that the next generation is not only good at creating new things but also thinking about the uses and effects of it.